Equity in cycle lane networks: examination of the distribution of the cycle lane network by socioeconomic index in Bogotá, Colombia. Issue 1 (2nd January 2018) - Parra, Diana C.; Gomez, Luis F.; Pinzon, Jose D.; Brownson, Ross C.; Millett, Christopher
ABSTRACT: The public network of bicycle lanes in Bogota Colombia, known as 'Cicloruta', is the largest in Latin America. Despite its success, disparities in regards to the distribution of routes by socioeconomic status (SES) of neighborhoods have not been examined. This exploratory analysis sought to assess the distribution and distance to the city network of bicycle lanes by neighborhood SES in urban blocks located in flat terrains. We conducted a spatial ecological analysis using secondary data obtained through geographic information systems from official databases. We calculated the shortest route from the centroid of each urban neighborhood block to the closest access point of the bicycle lane network. The median distance to the bicycle lane network from urban block centroids was 444m. This median distance ranged from 1, 062m for the most disadvantaged areas to 315m for the wealthiest, showing a clear difference in the spatial distribution. Results show wide variation in the distribution of bicycle lanes by SES, but particularly for the most disadvantaged areas. Improving the conditions for cycling in a more equitable manner may involve expanding the network of bicycle lanes for populations living in less advantaged areas.